Employee Performance Management System Characteristics with Performance Management System Effectiveness: Exploring the Mediating Role Of Fairness. (International Journal of Scientific Research and Management (IJSRM), 2017)
Based on expectancy theory, goal-setting theory and control theory we propose a model in which perceived fairness mediates the relationship between characteristics of employee performance management systems and their perceived effectiveness by employees. The model was tested on a sample of 3192 employees, using structural equation modelling. The findings advance research to the role and functionality of performance management systems by showing that (a) the manner in which performance management systems are shaped and executed is of fundamental importance for their effectiveness, (b) fairness partially mediates the relationship between performance management system characteristics and their effectiveness, and (c) the three motivational theories appear useful for understanding the consequences of performance management practices on individual employees.